Cryoglobulinemia Associated With Multiple Myeloma in a Dog Presenting With Epistaxis and Skin Lesions - Myrto Spyropoulou; Ivan Montanes‐Sancho; Adam G. Gow; Suzanne Bussey (Veterinary Medicine and Science)
ABSTRACT A 10‐year‐old female neutered Labrador Retriever presented with epistaxis, discoloration and crusting of the nose and a necrotic lesion on the lip. Bloodwork revealed pancytopenia, azotemia, hypoalbuminemia and hyperglobulinemia. Aggregates of amorphous basophilic material were seen in a room‐temperature blood smear which were not present in the sample after warming to 37°C, and grossly a cryoprecipitate was noted in the patient's serum at 4°C. This was interpreted as cryoglobulin. Computed tomography showed multiple heterogeneous lesions in the spleen. Cytology of the splenic lesions revealed marked plasma cell infiltration, consistent with neoplasia. Bone marrow aspiration revealed an increased proportion of plasma cells (approximately 38% of the total cells). Serum protein electrophoresis showed a monoclonal spike in the gamma globulin region. A diagnosis of multiple myeloma associated with cryoglobulinemia was made. The patient received palliative care with prednisolone while the owner was considering chemotherapy. However, she rapidly deteriorated and was euthanized. The combination of cryoglobulin precipitation and hyperviscosity syndrome was considered responsible for the patient's original symptoms. Cryoglobulinemia is an extremely rare phenomenon that is often associated with lymphoproliferative disorders. This report describes its association with multiple myeloma in a dog presenting with atypical initial signs.